Investigation on Teachers’ Perception of Augmented Reality as Interactive Media for Science Learning - Dwiyanti, Ulfa; Setiabudi, Agus; Prima, Eka Cahya (FKIP Universitas Lampung, 2021)
This article aims to find out the teacher's perception of Augmented Reality (AR) as an interactive science learning medium that can stimulate students' curiosity, passion and motivation, especially in the era of Covid-19 learning where learning is limited. This article used qualitative methods with a descriptive approach. The subjects in this study were 10 junior high school teachers with different grade levels in the city of Makassar. The study data was obtained using questionnaires sent via google form links with 20 question items. The results showed that indicator method used of science lessons, media used od science lesson, knowledge of AR media, fesibility AR media as science lesson, got an average score of 70 with excellent categories, 83 with excellent categories, 62 with Good categories, and 80 in excellent categories. So it can be said by applying AR media to Science materials believed to be able to foster the spirit and motivation of students so as to create an effective learning atmosphere.Keywords: teachers’ perception, augmented reality, covid-19 pandemic. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp245-255